2013
DOI: 10.1002/2327-6924.12039
|View full text |Cite
|
Sign up to set email alerts
|

CHD knowledge and risk factors among Filipino-Americans connected to primary care services

Abstract: Purpose To examine the baseline knowledge and risk factors of coronary heart disease (CHD) among Filipino‐Americans (FAs), and to identify the predictors of CHD knowledge. Data Sources A convenience sample of 120 FAs recruited from three primary care clinics in Las Vegas, Nevada between May and July, 2010. Participants were asked about their demographic data and presence of CHD risk factors using the Demographics questionnaire. CHD knowledge was examined using the Heart Disease Fact questionnaire. Conclusions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…This study was an assessment of blood glucose levels, but may not be generalizable to the population of Filipino Americans in the Northeast United States, since it was conducted in Hawaii. Dyslipidemia has been a common health issue among Filipino Americans, with one study finding a prevalence of 36.7% [33]. …”
Section: Discussionmentioning
confidence: 99%
“…This study was an assessment of blood glucose levels, but may not be generalizable to the population of Filipino Americans in the Northeast United States, since it was conducted in Hawaii. Dyslipidemia has been a common health issue among Filipino Americans, with one study finding a prevalence of 36.7% [33]. …”
Section: Discussionmentioning
confidence: 99%
“…The mean score obtained 22,23 on the HDFQ scale by the participants indicated an inadequate level of CHD risk factor knowledge among adult Omanis. Studies from other parts of the world have similarly reported low levels of knowledge and awareness of CHD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…22 The modified HDFQ instrument has also shown high internal consistency, with a Cronbach's alpha of 0.84. 23 In this study, the Cronbach's alpha coefficient was 0.86. The questionnaire was administered in both Arabic and English.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations